Arabic Digital Literature at the Touchstone of Genre Monitoring: Reflections and Comparisons (The International Journal of Educational Sciences and Arts, 2023)
This paper deals with the topic of Arabic digital literature from a genre perspective, looking at the extent to which its texts have sufficient characteristics to support its classification as an independent genre, by delving into an established question, which should not be skipped under any reason or pretext.The study contends that Arabic digital literature is still at the beginning of its path towards independence and the acquisition of a foundation that may be deemed unique. The Arabic digital writer still adheres to the paper style, drawn to the genres of written literature, as his texts do not include evidence of a deep assimilation of the characteristics of literature. It also lacks adequate absorption of its production and reception space and a clear distinction between the forms of expression provided by modern digital publishers, compared to what is provided by traditional paper carriers.Many Arab innovators continued to ruminate on the techniques of paper-based literary writing, arbitrarily transferring them to the computer world, without subjecting them to processes of experimentation and diligence that fit the new carrier. As a result, what they created were stylistically faded copies of texts, as if written or displayed on paper. This holds true despite the fact that few of them showed some boldness in synthesizing the distinctive artistic elements of different traditional genres, which make the digital space a window for creating very innovative and witty literary combinations.While many have taken advantage of some of the characteristics of digital expression, such as anonymity and interactivity, to create new textual forms that reveal large areas of daring and eagerness to cross some red lines, they have largely remained imprisoned by traditionally forged themes. Many of their texts also unfortunately remain tainted with some suspicion in regard to their legitimacy at the level of intellectual property, due to the intensification of piracy and plagiarism in the midst of the digital space.
Keywords: Digital Literature; Genre; Transmission; Written Literature